Análise imuno-histoquímica das proteínas VEGF e HIF-1α na doença periodontal - Vasconcelos, Roseane Carvalho (2012)
Periodontal disease is a complex inflammatory and infectious condition that immune host, front of the microbial aggressions, can lead to disease progression, resulting in tissue destruction. The tissue damage induces the release of regulatory molecules, which protective roles and / or destructive, including proteins VEGF (vascular endothelial growth factor vascular) and HIF-1 α (hypoxia-induced factor α -1). Thus, this study investigated, quantitatively and comparatively, the immunohistochemical expression of VEGF (vascular endothelial growth factor) and HIF-1 α (hypoxia induced factor 1-α), proteins involved in inflammation, angiogenesis and hypoxia, in human gingival tissues. Therefore, 75 samples of gingival tissues were examined. Thirty samples were chronic periodontitis, 30 with chronic gingivitis and 15 healthy gingival. After sections analysis, positives and negatives inflammatory and endothelial cells in the connective tissue were counted and converted into percentage. Data were statistically analyzed using Kruskal-Wallis test and Spearman correlation. The results showed that both proteins marked. It was observed higher immunoreactivity for HIF-1 α at chronic gingivitis and periodontitis specimens compared to healthy sites, however, no statistically significant differences were observed among them (p>0.05). The VEGF immunostaining showed similarity among the cases of periodontitis, gingivitis and healthy gingiva. Moderate and positive correlation statistically significant differences were verified for the expressions of VEGF and HIF-1α in gingival health (r = 0,529, p = 0.04). Thus, it can be conclude that possibly the route of HIF-1 α, is activated in periodontal disease may have involvement of the protein in pathogenesis and progression of disease, and that activation of VEGF, can be in addition to being triggered transcription by HIF-1 α may be also influenced by other additional factors such as the action of periodontal microorganisms endotoxins